Impact of COVID-19 Pandemic on Infectious Keratitis Outcomes: A Retrospective Multicenter Study in Tertiary Eye Hospitals of South India. Issue 11 (21st November 2021) - Christy, Josephine S.; Mathews, Priya; Rhagavan, Anita; Venugopal, Anitha; Manohar, Divya; Janakiraman, Anuja; Gandhi, Preethika; Nallobolu, Srujana; Akpek, Esen K.
Abstract : Purpose: The purpose of this study was to report the adverse effects of the COVID-19 pandemic on the clinical outcomes of infectious keratitis in South India. Methods: Two hundred fifty-eight patients presented with infectious keratitis at 6 tertiary care centers when strict travel restrictions were in place from March 24 to May 31, 2020. Case records were collected retrospectively and analyzed for demographics, type of initial treatment, length of delay in presentation, microbiological diagnosis, clinical course, and final treatment outcome. Results: The mean age of the patients was 49.2 years, with most of them (61.2%) being male. Forty-one patients (15.9%) did not receive any treatment for at least a week after the onset of symptoms. One hundred eight patients (41.9%) presented with severe ulcer (32 had a frank perforation). Resolution of the infection was achieved only in 103 patients (45.6%). A total of 90 patients (39.8%) with ulcers had a perforation, yet only 29 patients (32.2%) could receive keratoplasty because of the unavailability of donor tissues. At the end of 6-month follow-up, 47 patients had anatomical failure (loss of globe) and 12 additional patients had functional failure (total permanent vision loss). Conclusions: Delay in presentation and acute shortage of donor corneal tissues for emergency keratoplasty because of the COVID-19 pandemic had a grave impact, resulting in irreversible blindness in a significant number of patients.